EL APORTE DE LA CIENCIA AL ACERVO PROBATORIO EN MATERIA PROCESAL PENAL A FINALES DEL MILENIO (HUMANIZACIÓN) - Parra Quijano, Jairo (Revistas ICDP, 2026)
EL APORTE DE LA CIENCIA AL ACERVO PROBATORIO EN MATERIA PROCESAL PENAL A FINALES DEL MILENIO (HUMANIZACIÓN)